A ESCRITURA FEMININA NO CONTO SUL-RIO-GRANDENSE - Bittencourt, Gilda (Organon, 2004)
This work discusses literary representation made by women writers of Southern Brazilian literature from70’s and 80’s in the XXth century. Through these texts, we try both to identify recurrent subject matters whichexpress preoccupations inherent to feminine condition and to indicate some traces which show the existence of asomewhat different way of writing, as to revealing a rather particular sensibility in a women’s perception.